(Natural Antioxidant : Source, Chemistry, and Extraction Technology) - Lukman Junaidi (Warta Industri Hasil Pertanian, 2005)
Antioxidant are subtances that when present in food or in the body at low concentration compared to that of an oxidizable substrate markedly delay or prevent the oxidation of that substrate. The mechanism by which antioxidants protect food from oxidation is by scavenging of free radicals via donation of an electron or a hydrogen atom,or by deactivation of metal ions and singlet oxygen. Natually occuring inhibitors of oxidation in food generally originate from plant-based materials.Antioxydant can be classified into groups based on how they work and where they are found.There have been a number of assay mathods developed to measure the capacity of antioxidant as pure compounds or in extract.These methods foccus on different mechanisms of the antioxidant such scavenging of oxygen and hydroxyl radicals,reduction of lipid peroxil radicals,chelation of metal ions,or inhibition of lipid peroxidation.The very common methods used were:ORAC,OSI,DPPH ,and TEAC.There are three principle,techniques that may be used to extract naturally occuring antioxidant:extraction using solvent solid-phase extraction,and supercritial carbondioxida extraction